2011
DOI: 10.1074/jbc.m111.278119
|View full text |Cite
|
Sign up to set email alerts
|

NrdH-Redoxin Protein Mediates High Enzyme Activity in Manganese-reconstituted Ribonucleotide Reductase from Bacillus anthracis

Abstract: Background: Class Ib ribonucleotide reductase of the severe pathogen Bacillus anthracis can be loaded with manganese or iron.Results: The manganese form was 10-fold more active than the iron form in the presence of the physiological protein NrdH-redoxin.Conclusion: The manganese form is important in the life cycle of B. anthracis.Significance: The physiologically relevant form of ribonucleotide reductase controls B. anthracis proliferation and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(80 citation statements)
references
References 40 publications
(67 reference statements)
4
75
1
Order By: Relevance
“…NrdF has been known for some time to be able to self-assemble an active Fe III 2 -Y ⅐ cofactor from apo-NrdF, Fe II , and O 2 in a manner analogous to the corresponding ␤ (NrdB) in the class Ia RNRs (13,14). We have recently demonstrated with the Escherichia coli and Bacillus subtilis NrdFs (4,5), as have Sjöberg and co-workers (8) (16). In many, but not all, of the class Ib RNRs, NrdH can re-reduce the disulfide in ␣ produced concomitant with dNDP formation (Fig.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…NrdF has been known for some time to be able to self-assemble an active Fe III 2 -Y ⅐ cofactor from apo-NrdF, Fe II , and O 2 in a manner analogous to the corresponding ␤ (NrdB) in the class Ia RNRs (13,14). We have recently demonstrated with the Escherichia coli and Bacillus subtilis NrdFs (4,5), as have Sjöberg and co-workers (8) (16). In many, but not all, of the class Ib RNRs, NrdH can re-reduce the disulfide in ␣ produced concomitant with dNDP formation (Fig.…”
mentioning
confidence: 72%
“…Although the identification of the endogenous reductant has been reported in some of the studies, in most cases the activity of the class Ib RNR remained very low even with the endogenous reductant (6,8). We have chosen to examine the importance of manganese-versus iron-loaded cofactor in S. sanguinis class Ib RNR because this organism causes infective endocarditis, and deletion of a manganese transporter results in loss of virulence (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…anthracis NrdE, NrdF, and NrdI were expressed and purified as described earlier (29). NrdE was stored in 50 mM TrisHCl, pH 7.6, 20% glycerol, 2 mM DTT.…”
Section: General-b Anthracis Sterne 7700 (Pxo1mentioning
confidence: 99%
“…The equivalent nrdH gene in Bacillus is unlinked to the nrdI-nrdE-nrdF operon and located elsewhere on the chromosome. B. cereus NrdH was recently shown to be an efficient reductant of the manganese forms of B. cereus and B. anthracis class Ib RNRs (29). It has been shown that both subunits of the type Ib ribonucleotide reductase are essential for B. subtilis (14), and given the absence of a type Ia RNR in B. anthracis (30), it would be reasonable to assume that the same holds true for this bacterium.…”
mentioning
confidence: 99%